Предмет: Алгебра,
автор: pacha0208
12-2(x-3y)=x+y+2 1.2x+0.7y+1.4=0
Ответы
Автор ответа:
0
12-2х+6у=х+у+2
1,2х+0,7у+1,4=0
12-2х+6у-х-у-2=0
1,2х+0,7у+1,4=0
10+5у=3х
0,4(10+5у)+1,4=0
10+5у=3х
4+5у+1,4=0
10+5у=3х
5у=-5,4
10+5у=3х
у=-1,08
10-5,4=3х
у=-1,08
3х=4,6
у=-1,08
х=1,53
у=-1,08
1,2х+0,7у+1,4=0
12-2х+6у-х-у-2=0
1,2х+0,7у+1,4=0
10+5у=3х
0,4(10+5у)+1,4=0
10+5у=3х
4+5у+1,4=0
10+5у=3х
5у=-5,4
10+5у=3х
у=-1,08
10-5,4=3х
у=-1,08
3х=4,6
у=-1,08
х=1,53
у=-1,08
Похожие вопросы
Предмет: Физика,
автор: aleksanicol
Предмет: Математика,
автор: DanaArsyEva
Предмет: Математика,
автор: nastyakharisova64
Предмет: Математика,
автор: ladygafurova
Предмет: Литература,
автор: nataliyagracheva